Development Of Student Worksheets Using Ethnomathematics Approach On Prism Geometry For Middle School - H Mailili, Wahyuni; Hajerina; Nursupiamin; Sriayulisyah; Windra (Program Studi Tadris Matematika dan Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This research aims to produce the topic of space geometry, specifically Prisms, for eighth-grade on middle school students (SMP/MTs) while meeting the criteria of validity, effectiveness, and practicality. The research method used is the Research and Development (R&D) approach with the Plomp model, which includes several stages, namely preliminary investigation, design, development or construction, as well as testing, evaluation, and revision. Based on expert validation, the developed worksheet obtained an average score of 3.81, which falls into the valid category. The results of the final learning test show a success rate of 81.10%, which falls into the very effective category. Meanwhile, the analysis of the teacher response questionnaire shows a practicality level of 93.05% with a very practical category. The results of the student response questionnaire also showed a practicality level of 91.23% with a very practical category. Thus, it is proven to be valid, effective, and practical, to be used in the learning process